Scrutinizing Individual C- Trans Plus DRTA Method to Increase Student's Reading Comprehension - Mutakhirani - Mustafa (Institut Agama Islam Negeri Palopo, 2020)
The objective of this research is to explain the development of Individual C-Trans plus DRTA Method in improving students’ reading comprehension among the eighth-grade Students of SMP Negeri 40 Bulukumba. The researcher used A Classroom Action Research (CAR) in this research. The researcher had conducted two cycles, where each cycle consisted of two meetings. It employed a reading test as an instrument. A number of the subject of the researcher were 31 students in XI class. Those consist of 13 men and 18 women. The findings consisted tests, students’ reading comprehension, and observation results. The first cycle of the first meeting was 57,58 and the second meeting was 63,54 and then the researcher tried to do the next cycle and the result in cycle II that was increasing of students score. In cycle II of the first meeting was 77,90 and the second meeting was 81,61. The conclusion of the research using C-Trans plus DRTA is able to improve the students’ reading comprehension (main idea) at the eighth grade. It was proved by the students’ achievement in cycle II was higher than cycle I and D-Test where in cycle I the students’ mean score reading comprehension becomes first meeting was 57,58 and the second meeting was 63,54, cycle II of the first meeting was 77,90 and the second meeting was 81,61. Based on the research findings, the implementation of Individual C-Trans plus DRTA Method showed success in improving reading comprehension.